Developing B2B Social Communities Keys to Growth, Innovation, and Customer Loyalty - Brooks, Margaret; Lovett, John; Creek, Sam (Apress : Imprint: Apress, 2013)
Developing B2B Social Communities: Keys to Growth, Innovation, and Customer Loyalty explains why business-to-business companies need a robust online community strategy to survive and flourish in today's changing economy and shows you how to design and execute your company's strategy successfully. Seminars, publications, market research, and customer care centers remain important tools in every B2B firm's toolbox for understanding, attracting, and serving customers while keeping them loyal. But in a world of fierce global price competition, increasing transparency of business practices, and ever-rising complexity, these traditional customer interaction channels are no longer enough for most B2B companies. That's why smart organizations-both large and small-are tapping into online communities to gain a huge competitive advantage: the ability to get much closer to customers and become more valuable to them. Developing B2B Social Communities delves into the generators of business value in online communities: immediate customer access to expert information within the company and from other customers; inexpensive delivery of custom technical help; demonstrations of how customers can to get the most from their products; and forums where customers can share tips, air gripes, reveal unmet needs, and suggest improvements.   Three veteran community managers show you how to harness the knowledge of the crowd to help shape your company's strategic direction, develop new products and services, identify trends, sell more, serve customers more efficiently, and provide better product support. Fleshing out precepts with real-world examples and case studies, the authors detail the transformational opportunities-and pitfalls-for creating online communities.